If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x-1)-1=4x+5(-3+x)
We move all terms to the left:
9(x-1)-1-(4x+5(-3+x))=0
We add all the numbers together, and all the variables
9(x-1)-(4x+5(x-3))-1=0
We multiply parentheses
9x-(4x+5(x-3))-9-1=0
We calculate terms in parentheses: -(4x+5(x-3)), so:We add all the numbers together, and all the variables
4x+5(x-3)
We multiply parentheses
4x+5x-15
We add all the numbers together, and all the variables
9x-15
Back to the equation:
-(9x-15)
9x-(9x-15)-10=0
We get rid of parentheses
9x-9x+15-10=0
We add all the numbers together, and all the variables
5!=0
There is no solution for this equation
| 3p-6+6=5{p+4} | | 3x-21=6x+13 | | 111x-62=-2x+146 | | 20n=19n-11 | | -9+6+6a-a=3+6a | | 3x=x-105 | | 4×5×.5=m | | 6(2b-3)=54 | | 1/2+y=8 | | 2+3x+6x=2x+30 | | 4×5×.5=n | | 13/26=n/5 | | -2(-3s+6s)=3-s | | x^2+16x−46=0 | | -3c=21/4 | | 1/2y+4=16 | | 5(7n-3)=20 | | -10+6v=2v-5+3v | | 4(c–16)–6=2 | | 312(2x)=(2x^2)+(2x) | | 18-10j=78 | | 11z+15=-2z+54 | | 1+4x=13-2x | | 2-5n=n-3-5n+2 | | 8g-10=3g | | 5(x+10)-6=x+66 | | 11z+15=-2z=54 | | 60=100-100/25c | | 1/3x-2=9 | | (4m+9)−3(2m−5)=(4m+9)−3(2m−5)= | | 300p+300p-10+p-590=1 | | (-18)=(-6)+4x |